Study of Eye Movements Abnormalities in Epilepsy - Mrabet, S.; Abdelkefi, I.; Sghaier, I.; Atrous, A.; Abida, Y.; Souissi, A.; Gharbi, A.; Nasri, A.; Gargouri-Berrechid, A.; Kacem, I.; Gouider, R. (Neuro-ophthalmology (Amsterdam : Aeolus Press. 1980), 2025)
Idiopathic epilepsy (IE), is a group of epileptic syndromes with no structural brain lesion, but with microstructural changes in neuronal networks leading to neuropsychological consequences. Therefore, the assessment of saccadic eye movements can provide insight into the integrity of cerebral networks as it involves large cortical and subcortical brain areas and circuitries. Describe saccadic eye movement abnormalities in patients with IE and correlate them with disease characteristics and antiseizure medication. Case-control study including IE patients followed in the Neurology Department of Razi University Hospital and healthy controls matched. Participants underwent a recording of saccadic eye movements. Pursuit, prosaccade, and anti-saccade tasks were performed. 115 patients and 98 matched healthy controls were included. The gender ratio (male to female) was 0.6. The mean age at onset was 16.3 ± 12 years. Diagnosed epileptic syndromes were juvenile myoclonic epilepsy (JME), epilepsy with generalized tonic-clonic seizures, childhood absence epilepsy, temporal lobe epilepsy, frontal lobe epilepsy, and rolandic epilepsy. Saccadic eye movements were impaired in 52.2% of our patients and significantly more altered in those with JME ( = .021). Prolonged horizontal saccades latencies were the most frequent eye movement abnormalities (32.1%), followed by altered horizontal smooth pursuit (22.6%). A positive correlation was found between age at eye movements recording, age at onset, disease duration, global cognitive impairment, and saccadic eye movements. However, no definite relationship was identified. Saccadic eye movement illustrates extending anatomic alterations in IE including frontal and temporoparietal cortical areas and cortico-subcortical circuits. Eye movement recording is a useful and reproducible tool in the assessment of epileptic patients and provides a better understanding of neuronal mechanisms in epilepsy.